ARTIFICIAL INTELLIGENCE IN MEDICINE: A NEW STAGE IN MODERN DIAGNOSTICS - Buronov Shukurillo Bakhtiyor ugli; A’zamqulova Marjona Sherali qizi (Journals Park Publishing, 2026)
This article discusses the role and importance of artificial intelligence (AI) technologies in the medical field, in particular in diagnostic processes. The possibilities of using artificial intelligence algorithms in modern medical imaging, laboratory analysis, and clinical decision support systems are analyzed. The advantages, limitations, and future prospects of artificial intelligence are also considered on a scientific basis.
Keywords: Artificial intelligence algorithms, medical diagnostics, laboratory, resources, oncological diseases, DNA analysis, diabetes, cardiology, MRI, reactive and proactive medicine, surgery, Harvard Medical School, education, industry, research, scientific research.